Best Answer

Are you sure the equation is not: -3x2 - 2x + 5 = 0?

Which is the same as 3x2 + 2x - 5 = 0 which factorises into (3x + 5)(x - 1) with solutions x = 1 and x = -5/3 = -1 2/3 ~= -1.67.

As stated there are no real solutions to the equation, only complex solutions: x = -1/3 + i sqrt(14)/3 and x = -1/3 - i sqrt(14)/3

Q: Solve -3x² -2x -5 equals 0?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

2x+3x-2=0=5x=0+2=5x=2=5x_5=2_5=x=0.4

2x(3x+6) = 0 x = 0 or x = -2

3x - 2x + 4 = 0 3x - 2x = -4 x = -4

3x2 + 2x = 16 ∴ 3x2 + 2x - 16 = 0 ∴ 3x2 - 6x + 8x - 16 = 0 ∴ 3x(x - 2) + 8(x - 2) = 0 ∴ (3x + 8)(x - 2) = 0 ∴ x ∈ {-8/3, 2}

x = 4 and y = 0

Related questions

2x+3x-2=0=5x=0+2=5x=2=5x_5=2_5=x=0.4

2x(3x+6) = 0 x = 0 or x = -2

3x - 2x + 4 = 0 3x - 2x = -4 x = -4

6x2 = -7x -2 6x2 + 7x + 2 = 0 6x2 + 3x + 4x + 2 = 0 3x(2x + 1) + 2(2x + 1) = 0 (2x + 1)(3x + 2) = 0 2x + 1 = 0 or 3x + 2 = 0 So, x = -1/2 or -2/3

3x2 + 2x = 16 ∴ 3x2 + 2x - 16 = 0 ∴ 3x2 - 6x + 8x - 16 = 0 ∴ 3x(x - 2) + 8(x - 2) = 0 ∴ (3x + 8)(x - 2) = 0 ∴ x ∈ {-8/3, 2}

x = 4 and y = 0

6xx - 13x + 6 = 0 6x2 - 13x + 6 = 0 (3x-2)(2x-3)=0 3x-2=0 or 2x-3=0 3x=2 or 2x=3 x=2/3 or x=3/2 x=0.667 or x=1.5

3x(2x + 1)

6x2 + 9x = 0 3x(2x + 3) = 0 3x = 0 or 2x + 3 = 0 x = 0 or x = -3/2

y= -2x

3x2 + 2x - 8 = 0 is a quadratic equation.

3x + y + 1 = 0y = - 3x - 12x - 3y + 8 = 03y - 2x - 8 = 03y = 2x + 8y = 2x/3 + 8/3-3x - 1 = 2x/3 + 8/3-9x - 3 = 2x + 8-11x = 11x = -1y = -3x - 1 = 3 - 1 = 2The graphs intersect at the point (-1, 2).